Valuation and Appreciation of Biodiversity: The “Maintenance of Options” Provided by the Variety of Life - Faith, Daniel P. (Frontiers in Ecology and Evolution, 2021)
“Nature’s contributions to people” (NCP) is an important expansion beyond the standard ecosystem services framework, particularly as a pathway to better address global/regional biodiversity values. NCP18, “maintenance of options,” refers broadly to the capacity of ecosystems, habitats, species, or genotypes to keep options open to support a good quality of life. “Biodiversity,” interpreted as living variation, is an important, but under-appreciated, aspect of “maintenance of options.” IPBES refers to “the “option values of biodiversity,” that is, the value of maintaining living variation in order to provide possible future uses and benefits.” IPBES assessments include biodiversity option value, and use phylogenetic diversity (PD) as an indicator of change in status of NCP18. At the same time, IPBES notes the need for greater appreciation of option values of biodiversity. Popular ecosystem services framings forget the long history of consideration of these global benefits of biotic diversity to humanity, and their normative links. Popular ecological definitions mean that many current valuations of “biodiversity” neglect the benefits of biodiversity-as-variety. Economic valuations of “biodiversity” typically have focused on ecosystem aspects, not variety; related ecosystems framings value “biodiversity” with a focus on those critical elements relating to functioning of ecosystems. Greater appreciation of biodiversity option value and NCP18 may depend on clearer messaging from academia, better highlighting of the link between biodiversity and intergenerational justice, and greater communication of stories of past surprising discoveries of benefits from species that highlight biodiversity as an ongoing source of future benefits. An important pathway for better appreciation of insurance and investment benefits of variety is to understand and communicate the reasons why we value these benefits from variety. Biodiversity-as-variety is valued because we care about the welfare of future generations.